2015
DOI: 10.3390/w7094724
|View full text |Cite
|
Sign up to set email alerts
|

Flow Patterns in an Open Channel Confluence with Increasingly Dominant Tributary Inflow

Abstract: Despite the ratio of incoming discharges being recognized as a key parameter in open-channel confluence hydrodynamics, little is known about the flow patterns when the tributary provides more than 90% of the total discharge. This paper offers a systematic study of flow features when the tributary becomes increasingly dominant in a 90° confluence with a fixed concordant bed. Large-eddy simulations are used to investigate the three-dimensional complex flow patterns for three different discharge ratios. It is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 31 publications
3
46
0
3
Order By: Relevance
“…The experimental tests of Birjukova et al [23] were reproduced by Brito et al [32], comparing the results obtained with different turbulence closure models for solving the RANS equations. More recently, Schindfessel et al [33] used LES of the OpenFOAM suite to investigate the flow patterns for three different Q r , considering the experimental tests by Schindfessel et al [22]. They demonstrated that the tributary flow impinges on the opposing bank when the tributary flow becomes sufficiently dominant, causing a recirculating eddy in the upstream channel of the confluence, which induces significant changes in the incoming velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental tests of Birjukova et al [23] were reproduced by Brito et al [32], comparing the results obtained with different turbulence closure models for solving the RANS equations. More recently, Schindfessel et al [33] used LES of the OpenFOAM suite to investigate the flow patterns for three different Q r , considering the experimental tests by Schindfessel et al [22]. They demonstrated that the tributary flow impinges on the opposing bank when the tributary flow becomes sufficiently dominant, causing a recirculating eddy in the upstream channel of the confluence, which induces significant changes in the incoming velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al (2016) also observed a clear hump in the transverse velocity spectra, very similar to our observations in the centre of the channel (Figures 11B and 11C). Unfortunately, comparison with other confluences is limited as very few studies at confluences have provided a detailed turbulent analysis of the lateral velocity component in the mixing zone, with the studies of Schindfessel et al (2015) and Yuan et al (2016) in 90°laboratory junctions and modelling studies being the exception.…”
mentioning
confidence: 99%
“…The mixing of the two inflows is analysed by setting the dimensionless concentration of passive scalar at 1 in one inflow and at 0 in the other. As the Froude number is lower than 0.3, we use a rigid lid assumption [7] for the free surface.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In the last decade, 3D numerical methods have shown their ability to fairly compute the hydrodynamics of the flow in open-channel confluences [5], [6], [7], [1]. However detailed databases of passive scalar concentration within such confluences and downstream branches is lacking in the literature and thus does not permit to validate the 3D numerical codes, either advanced (LES or DES) or more operational codes (RANS) regarding their capacity to fairly reproduce the mixing processes.…”
Section: Introductionmentioning
confidence: 99%